Tuning the Optical Properties of Phenanthriplatin: Towards New Photoactivatable Analogues. Issue 11 (16th August 2017) - Cerón‐Carrasco, José Pedro; Jacquemin, Denis
Abstract: The activity of traditional bifunctional platinum‐based drugs is based on a double binding attack of DNA strands that eventually damages the genetic code. Unfortunately, such therapy comes with severe side effects, which drastically limit its efficiency and more importantly, its large‐scale applicability. One emerging alternative is the use of monofunctional platinum complexes based on phenanthriplatin, a new molecule that develops a potent toxicity in tumorous cells by reacting with one DNA base only. Herein, we use theoretical tools to assess the optical properties of phenanthriplatin as well as a series of analogues in an effort to pave the way to their use in photoactivated chemotherapy. In a first step, the absorption signatures of both isolated and DNA‐embedded drugs are predicted through ab initio calculations. Two nitro derivatives are shown to activate a charge transfer from the DNA to the drug and might consequently initiate a cascade of photodamage events. In a second step, we performed molecular dynamics simulations that reveal that such structural change is enough to perturb the DNA‐binding mode. The biological implications of these results in the framework of the design of novel photoactivatable drugs are discussed. Abstract : Push or pull? Ab initio calculations and molecular dynamics simulations were used to quantify the tunability of the optical properties of the anticancer drug phenanthriplatin. This investigation indicates that strong‐electron‐acceptor substituents, such as nitro functional groups, might be used to activate photodamage bands, although the biological activity of such drugs is likely significantly affected by any change in the phenanthridine ring.